Detection of emergency situations during the work of batch vacuum apparatus - Прокопенко, Юрій Володимирович; Ладанюк, Анатолій Петрович; Сокол, Ростислав Михайлович (Technology audit and production reserves, 2015)
Modern requirements for control of sugar technological complexes make the task of development and implementation of innovative control systems. Solution of new challenges is fully possible only when using intelligent control systems. The promising way is the development and implementation of control systems based on the principles of situational control. Use of such systems allows creating intelligent multi-agent system, based on a knowledge base of agent environment. It was designed and built two-level frame structure of detection of conflict situations for the batch vacuum apparatus control. The resulting two-level frame control structure defines emergency and conflict situations in the format of environment categories: actions – A, situations – S. Such structure of frame building allows create multi-level control systems and enables rapid change control system through the mechanism of scenarios. Algorithms of frame of conflict situations created with the help of language of situational control and situational description of the object. Application of the proposed frame structure in the case control systems (agent systems) allow more efficient, at a qualitative level, to monitor the mass crystallization of sugar, integrate equipment in the technological complexes, as well as in the multi-level system of production control. A promising area of application of multi-level systems is their use in decision-making systems, organizational and technical systems.